Тень конторы: [роман] / Андрей Ильин - Ильин Андрей Александрович (Обет молчания, 2003)
Экземпляры: ф.12 (2003) / Инвентарный номер: 44790 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: И 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44